Combined ultrasound and photoacoustic imaging of blood clot during microbubble-assisted sonothrombolysis - Das, Dhiman (J Biomed Opt, 2019)
Blockage of healthy blood vessels by blood clots can lead to serious or even life-threatening complications. The use of a combined ultrasound (US) and photoacoustic (PA) imaging was explored for blood clot monitoring during microbubble-assisted sonothrombolysis. PA imaging is an emerging hybrid imaging modality that has garnered the attention of the biomedical imaging community in recent years. It enables the study of the composition of a blood clot due to its sensitivity toward optical absorption. Here, in vitro imaging of the side of a blood clot facing the microbubbles was done over time. The US and PA signal-to-noise (SNR) ratio value changes during microbubble-assisted sonothrombolysis were studied for two different local environments: blood clot in deionized water and blood clot in blood. In the first case, US and PA SNR values increased by 4.6% and reduced by 20.8%, respectively after 30 min of sonothrombolysis treatment. After 10 min of sonothrombolysis treatment of the blood clot in blood, the US and PA SNR values increased by 7.7% and 38.3%, respectively. The US and PA SNR value changes were recorded in response to its local environment. This technique can be used to determine the final composition of the blood clot which may, in turn, help in the administration of clot-dissolving drugs.